Effects of Presowing Seed Treatments for Better Crop Establishment in Summer Groundnut - K.K. DHEDHI,; C.J. DANGARIA,; G.J. PARSANA,; A.K. JOSHI, (Seed Research, 2026)
Two seed lots of groundnut (Arachis hypogaea L.) viz., fresh seed having high germination, vigour and revalidated seed (low vigour) were subjected to presowing seed treatments and their efficacy was evaluated during summer seasons of 2003, 2004 and 2005. Presowing seed invigoration by hydration for 16 h and air drying at room temperature followed by dressing with Thiram (75% DS) @ 0.25 per cent registered consistently and significantly higher pod yield than the untreated seeds in revalidated seed. The higher pod yield was resulted from significantly improved germination, speed of emergence, per cent field emergence, ultimately the better crop establishment and in turn higher plant stand. The beneficial effects of hydration followed by Thiram dressing were more pronounced in the low vigour seed lot (revalidated) than in the high vigour lot (fresh). The study highlighted the efficacy of hydro-priming followed by Thiram dressing.